Commercial Fiber Products Derived Free-Standing Porous Carbonized-Membranes for Highly Efficient Solar Steam Generation - Lin, Xiaofeng; Yang, Meijia; Hong, Wei; Yu, Dingshan; Chen, Xudong (Frontiers in Materials, 2018)
Herein, the free-standing porous carbonized-membranes (CMs) derived from a series of commercial fibre products including airlaid papers, cellulose papers and cleanroom wipers by one-step carbonization at 160 ℃ have for the first time explored as independent solar absorbers to realize highly efficient solar steam generation. These newly-developed CMs not only exhibit the strong absorption (low reflectance) and rapid transport of vapour/liquid, but also possess the restricted thermal diffusion. All these merits render CMs with excellent evaporation performance for solar steam generation. Particularly, the CMs derived from carbonized cellulose papers (CCPs) exhibits the best performance, which affords the water evaporation rate of 0.959 kg·m−2·h−1 and the energy conversion efficiency of 65.8 % under 1 kW·m-2 solar illumination, due to the higher light absorption (92.20 %) and lower thermal conductivity (0.031 W·m-1·K-1) competing favorable with those of the Au nanoparticles-loaded airlaid papers (Au-APs, 0.856 kg·m−2·h−1, 58.7 %). Due to the low-cost, recyclability and highly efficient evaporation performance, the CMs, especially the CCPs, show great potential as solar absorbers for large-scale application of solar steam generation.